Chemical, physical and biological soil properties, indicators of the status of different ecosystem in a high terrace of the Meta department (Orinoquia, 2018)
In the evaluation of the chemical, physical and biological properties as soil quality indicators for agroforestry systems, three systems of land use were valued. These systems are located in high terrace soils in the La Libertad de Agrosavia were evaluated: forest, system agroforestry (SAF) and grassland. Soil samples were taken at two depths 0-10 cm (P1) and 10-20 cm (P2). Chemical and physical variables were measured, microbial counts were made of fungi, bacteria, actinomycetes and mesoinvertebrates. These organism were identified at family and species level. Initially, a descriptive analysis of the data was performed and interpreted according to the reported reference values. The statistical analysis was carried out through Principal Component Analysis (PCA), variance analysis and Duncan’s mean comparison test (for which statistical software R version 3.1.2 (package ADE4 1.4.5) and INFOSTAT were used. 2014I). Chemical variables were selected: pH, exchangeable aluminum (AlH), phosphorus (P), calcium (Ca), magnesium (Mg), potassium (K), boron (B), sulfur (S), sodium (Na), zinc (Zn), effective cation exchange capacity (CICE) and the physical variables hydraulic conductivity (CH), bulk density (DA), mesoporosity (MES), total porosity (PT), saturation (SAT), field capacity (CC), available humidity (HD), microporosity (MIC), permanent wilting point (PMP), percentage of sand and clay, which allow to separate the systems in terms of soil quality. In the SAF, moderate chemical quality was found, represented by high pH values (5.30), low AlH (1.02 Cmol / kg), low contents of Ca in P1 (1.49 Cmol / kg) and P2 (0, 71 Cmol / kg), under Mg in P1 (0.49 Cmol / kg) and P2 (0.21 Cmol / kg) and, the highest values found of S (13.08 mg / kg) and Zn (0.70 mg / kg) in P2. In turn, the SAF showed low physical quality with DA values of 1.34 g / cm3 in P1 and 1.46 g / cm3 in P2. The biological variables did not contribute to the differentiation between systems, however, the forest showed a greater number of actinomycetes and arbuscular mycorrhizal fungi (AMF) associated with greater assimilation of nutrients such as P.
Keywords: Agroforestry system; SAF; forest; grassland; indicator